2021
DOI: 10.4103/jfmpc.jfmpc_2227_20
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and practices regarding dietary habits among medical and non-medical university students

Abstract: Background: Medical students even though being aware of the importance of well-balanced nutrition do tend to have laxity in practicing it themselves leading to poor nutrition. The aim of this study was to compare the awareness and knowledge of dietary habits among medical and non-medical students. Methods: This cross-sectional study was carried out in two universities in the Jeddah province, King Saud bin Abdulaziz University for Health Sciences (KSAU-HS) and King Abdul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…Of interest are the differences between participants from health and non‐health‐related majors, where, in the present study, the knowledge, attitudes, and practices, as well as willingness to change, were better among the health‐related major participants. These findings are in line with other studies showing a positive effect of a medical field of study on lifestyle behaviours 41 . Although larger studies with representative samples are needed to better characterise the behaviour of young adults regarding sustainable diets in the UAE, the results of the present study suggest the need for public health programs and interventions aiming to promote sustainable diets.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Of interest are the differences between participants from health and non‐health‐related majors, where, in the present study, the knowledge, attitudes, and practices, as well as willingness to change, were better among the health‐related major participants. These findings are in line with other studies showing a positive effect of a medical field of study on lifestyle behaviours 41 . Although larger studies with representative samples are needed to better characterise the behaviour of young adults regarding sustainable diets in the UAE, the results of the present study suggest the need for public health programs and interventions aiming to promote sustainable diets.…”
Section: Discussionsupporting
confidence: 91%
“…These findings are in line with other studies showing a positive effect of a medical field of study on lifestyle behaviours. 41 Although larger studies with representative samples are needed to better characterise the behaviour of young adults regarding sustainable diets in the UAE, the results of the present study suggest the need for public health programs and interventions aiming to promote sustainable diets. Such programmes should address the complex nature of behavioural changes, which according to the Health Belief Model, include perceived threat, benefits, barriers, and self-efficacy.…”
Section: Discussionmentioning
confidence: 76%
“…Many students work in part-time and report high levels of stress, aspects that might explain this association. Poor time management has been reported as a barrier to a healthier eating style [ 39 , 40 ] with a large proportion of university students perceiving their lifestyles as moderately-highly stressful and linked to the lack of proper time management [ 41 ]. Also, experiences of stress in university students (young adults) have been related to a poorer capability of eating in response to internal signals of hunger and satiety, which in turn, appears to result in higher emotional (less intuitive) eating [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite this knowledge, most of the participants consumed carbonated beverages and fast food. In a study conducted by Saeed Ali Alghamdi et al (14) reported that 34.6 percent consumed vegetables daily while 47.1 percent on some days and 14 percent rarely consumed green vegetables. About 53.7 percent participants in their study consumed fast foods infrequently and 22.1 percent daily in a week.…”
Section: Dietary Practicesmentioning
confidence: 99%
“…In a study conducted by Eman Mokbel Alissa et al (13) found that when asked if they engaged in physical exercise, 50 percent of the students indicated "No", 43 percent said 1-3 times and only a small percentage said 4-6 times and 7 times. In a study conducted by Saeed Ali Alghamdi et al (14) showed that 22.1 percent of medical students exercised regularly, 41.9 percent occasionally, and 23.5 percent infrequently. When asked which sport participants most frequently engaged in, medical students most frequently selected aerobics (43.7%), followed by ball sports.…”
Section: Physical Activity Practicesmentioning
confidence: 99%